IMPLEMENTATION OF SEQUENTIAL SEARCHING ALGORITHMS ON SNABID SYSTEMS - Amartya Bambang Kusuma; Joko Iskandar; Yayak Kartika Sari (STKIP PGRI TULUNGAGUNG, 2023)
SNABID is a store that operates in the field of food industry, where its main activity is to produce and sell a variety of bakeries and cakes. SNABID has an online store website in which there is a catalog of products provided. The SNABID system has a product catalog search feature. The aim of this research is to implement the Sequential Searching algorithm to facilitate the search of products in the product catalog menu within the SNABID online store website. The phase of Sequential Searching algorithm is to determine the amount of data stored on an array, perform repetitions, perform matching of data on the array. If the data is the same as the one you are looking for, it means that the data has been found successfully. On the other hand, if until the end of the repeat does not have the same data as the one sought, it means that no data was found. The result of this research is that Sequential Searching algorithms can be applied to product searches based on product names and run well according to planning and almost all problems on the manual sales system can be solved with the presence of this SNABID system. In terms of storage, processing and processing become more efficient.